Stable Hydrogen‐Bonded Cobalt‐porphyrin Framework for High‐Performance Electrochemical Detection of Carcinoembryonic Antigen - Youfa Wang; Jie Han; Geoffrey I. N. Waterhouse; Huiwen Gu; Rui Wang; Shuang Wu; Pengfei Dong; Vijaya Raghavan; Jin Wang (Aggregate)
ABSTRACT The accurate and sensitive detection of low‐abundance cancer‐related biomarkers in blood remains a key technical challenge in clinical applications. Herein, a simple and accurate sandwich‐type electrochemical immunosensor based on a stable hydrogen‐bonded cobalt‐porphyrin framework (Co‐HOF) was successfully developed for the ultrasensitive detection of the cancer‐related biomarker, carcinoembryonic antigen (CEA). The antibody‐modified Co‐HOF forms a sandwich structure with the CEA aptamer electrode exclusively in the presence of CEA, enabling the specific electrochemical detection of CEA. The electrochemical signal increased linearly with the concentration of CEA, demonstrating a wide linear range (0.001–50 ng mL−1) and a low detection limit (0.22 pg mL−1), surpassing the performance of commercial ELISA kits and most reported detection methods. The sensor was successfully employed for CEA detection in spiked human serum, with recoveries ranging from 85.04% to 105.20%. Additionally, we collected blood samples from colorectal cancer patients and healthy individuals to clinically validate the sensor, observing that CEA levels increased with cancer progression. The sensor detection results showed strong consistency (R2 = 0.995) with those obtained from commercial ELISA kits, demonstrating the proposed sensor's practicality for clinical detection of CEA and related cancer biomarkers.